PROFESIONALITAS GURU SEKOLAH DASAR ATAS HUKUMAN DAN HADIAH: STUDI KASUS DI SEKOLAH DASAR NEGERI - Elvita Erika; Lukas Lukas; Puspita Dewi Debi; Yuhandra Conli Kosdamika; Rijaya Rijaya (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2023)
The purpose of this study was to analyze the views of public elementary school (SDN) teachers on punishment and rewards within the framework of teacher professionalism. The research method used is qualitative, with two data collection techniques: interviews with research subjects and direct observation. This study found that teachers have a constructive view of reward and punishment. With this constructive view, giving gifts and punishments has improved student behavior. The technique of giving punishments and rewards is carried out democratically, namely by providing socialization to students and involving students' commitment to agreeing on the rules that have been socialized. The punishment given to students was giving advice, saluting the flag, throwing trash in its place, sweeping and cleaning the classroom, memorizing Pancasila, singing the national anthem Indonesia Raya, and cleaning the toilets. In contrast, reward giving is praise, a book, cash, food, and high marks.